INCREASING THE ENGLISH-LANGUAGE CONTENT ON FRANCOPHONE MINORITY SCHOOL BOARDS’ WEBSITES IN CANADA: A LONGITUDINAL STUDY (2008-2016) IN SUPPORT OF NON-FRENCHSPEAKING PARENTS AND GUARDIANS - Rocque, Jules (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2019)
This paper focuses on the results of a longitudinal study examining the English-language content of Francophone minority school boards’ websites throughout Canada, mindful of the changing profile of the boards’ parental population. A document analysis research approach was used to analyse how the content destined for a non-French-speaking audience has evolved, enabling the audience to have access to new and pertinent information. It was observed that the majority of boards in Western Canada and Ontario have increased the presence of English on their websites. Atlantic Canada (with the exception of New Brunswick) has followed this trend. It is worth noting that other languages and content areas have shown up on the web sites, confirming the changing demographics of Francophone minority communities in Canada.